Mobile App–Based Intervention for Adolescents With First-Episode Psychosis: Study Protocol for a Pilot Randomized Controlled Trial - Barbeito, Sara; Sánchez-Gutiérrez, Teresa; Mayoral, María; Moreno, Miguel; Ríos-Aguilar, Sergio; Arango, Celso; Calvo, Ana (Frontiers in Psychiatry, 2019)
Introduction: Previous studies have shown an improvement in the access to treatment for patients with first-episode psychosis (FEP), specifically young patients, through mobile app–based interventions. The aim of this study is to test the effectiveness of a mobile app–based intervention to improve community functioning in adolescents with FEP. Mobile app–based interventions could increase quality of life and disease awareness, which improve adherence to treatment and reduce the frequency of relapses and rehospitalizations in adolescents with FEP. Methods: This article describes a mobile app treatment and the pilot trial protocol for patients with FEP. We will perform a single-blind randomised clinical trial (RCT) including patients with FEP aged 14-19 years recruited from Gregorio Marañón Hospital, Madrid, Spain. Patients will be randomly assigned to an intervention group, which will receive treatment as usual plus 5 modules of a psychological intervention through the mobile app (psychoeducation, recognition of symptoms and prevention of relapses, problem solving, mindfulness, and contact wall), or to a control group (standard care). The effectiveness of the intervention will be assessed by means of an extensive battery of clinical tests at baseline and at 3 months of follow-up. The primary outcome is reduction in psychotic and depressive symptoms; secondary outcomes comprise adherence, awareness, use of drugs, and quality of life. Data will be analysed on an intention-to-treat (ITT) basis. Mixed model repeated-measures analysis will be used to explore the following effect: group  time interaction between the control group and the intervention group for clinical and functional variables during the follow-up period. Discussion: This is an innovative study for the assessment of a psychological intervention through a mobile app for patients with FEP during the critical period. This pilot RCT is intended to be a precursor to larger studies, which in turn could facilitate dissemination of mobile app therapy for patients with FEP. Ethics and dissemination: The local ethics committee approved the study protocol. All participants must sign the informed consent, to participate. After finalizing the study, the results will be published.